2022
DOI: 10.1126/scitranslmed.abl3836
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab induces HIV latency reversal in people living with HIV and cancer on antiretroviral therapy

Abstract: In people living with HIV (PLWH) on antiretroviral therapy (ART), virus persists in a latent form where there is minimal transcription or protein expression. Latently infected cells are a major barrier to curing HIV. Increasing HIV transcription and viral production in latently infected cells could facilitate immune recognition and reduce the pool of infected cells that persist on ART. Given that programmed cell death protein 1 (PD-1) expressing CD4 + T cells are preferentially infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 41 publications
1
64
0
Order By: Relevance
“… 43 Emerging correlative results from the CITN-12 study indicate that pembrolizumab can reverse the latency of HIV in vivo. 44 This study showed no evidence of HIV clonal expansion despite latency reversal, which provides additional safety data.…”
Section: Discussionmentioning
confidence: 56%
“… 43 Emerging correlative results from the CITN-12 study indicate that pembrolizumab can reverse the latency of HIV in vivo. 44 This study showed no evidence of HIV clonal expansion despite latency reversal, which provides additional safety data.…”
Section: Discussionmentioning
confidence: 56%
“…The expression of IRs is a hallmark of Tex (20,22,23) (14), and coexpression of IRs has been associated with HIV-1 disease progression (15,25,29,30,32) and cancer severity (49)(50)(51). ICB has demonstrated promising results in the cancer field (40,41), but the use of ICB as an HIV-1 cure intervention remains unclear (34,(43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of IRs is a hallmark of Tex (20,22,23) (14), and co-expression of IRs has been associated with HIV-1 disease progression (15,25,29,30,32) and cancer severity (4951). ICB has demonstrated promising results in the cancer field (40,41), but the use of ICB as an HIV-1 cure intervention remains unclear (34,4347). Understanding the dynamics of IRs expression in the context of CD8+ T-cell function in PLWH on ART is essential to guide target identification in developing widely applicable and precise HIV-1 cure immunotherapies based on ICB (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies to immune checkpoints, either alone or in combination, have also been shown to reverse HIV latency using both in vitro models and patient‐derived cells 38–40 . Blockade of PD‐1 with the anti‐PD‐1 antibody pembrolizumab was recently shown in a clinical trial to induce expression of both cell‐associated unspliced HIV RNA and plasma RNA in PWH on ART 41 . Antibodies to immune checkpoints can also increase HIV‐specific T‐cell function ex vivo 42 and in vivo; 43 however, whether this increase in HIV‐specific T‐cell function can also clear infected cells in vivo remains unknown.…”
Section: Enhancing Potency Function and Specificity Of Lrasmentioning
confidence: 99%